Antihyperuricemic effect of dietary polyphenol sinapic acid commonly present in various edible food plants. Issue 2 (17th December 2019) - Ishaq, Muhammad; Mehmood, Arshad; Ur Rehman, Ashfaq; Dounya Zad, Oumeddour; Li, Jiayi; Zhao, Lei; Wang, Chengtao; Hossen, Imam; Naveed, Muhammad; Lian, Yunhe
Abstract: The present study was conducted to evaluate the antihyperuricemic effect of sinapic acid (SA). The results showed that SA potently inhibited xanthine oxidase (XOD) in a dose‐dependent manner by entering the enzyme active site and thwarting the entrance of the substrate. These results were further confirmed by the quantum chemical descriptors analysis and 1 H NMR titration analysis. The in vivo results indicated that SA not only has the potential to inhibit serum and hepatic XOD ( p < .05), but also remarkably lowered serum and urine uric acid levels at 50 and 100 mg/kg bw. Furthermore, SA regulated serum creatinine and blood urea nitrogen levels to normal and lowered inflammation in the renal tubules. Thus, the utilization of SA as an antihyperuricemic agent may have considerable potential for the development of functional foods for the possible treatment of hyperuricemia. Practical applications: Plant‐derived bioactive compounds have multiple health benefits. The present study assesses the effects of sinapic acid against hyperuricemia. The results suggested that sinapic acid may have a strong protective effect against uric acid‐related complications and may be used for the formulation of functional foods. However, further mechanistic studies are required to verify this hypothesis. Abstract : Sinapic acid possesses anti‐hyperuricemic effect via inhibiting XOD enzyme in vitro and in PO‐induced hyperuricemic mice